Tax interactions among Belgian municipalities: does language matter? - Marcel Gérard; Hubert Jayet; Sonia Paty (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper tests the existence of strategic interactions among municipalities using a panel of Belgian local tax rates from 1985 to 2004. A special emphasis is put on the role of the language spoken in the various municipalities. Our results first confirm previous findings for Belgium suggesting that municipalities interact with each other over the two main local tax rates, the local surcharge on the (labour) income tax rate and the local surcharge on the property tax. Using tools of spatial econometrics and an original methodology for specifying weights matrices, we find out that municipalities are sensitive to tax rates set by their close neighbours only. We also reject the hypothesis that the language does not matter: in the within model and for the local income tax rate, the intensity of interactions is shown to be lower between municipalities speaking different languages than between municipalities speaking the same language. That observation is particularly relevant for today Belgium and might be viewed as a contribution to the ongoing debate on the regionalisation or partial decentralization of some taxes.
Keywords: H24; H31; H71; 330; Tax interactions; panel data; spatial econometrics; local tax rates; tax competition; yardstick competition; Gemeindesteuer; Steuertarif; Steuerwettbewerb; Yardstick Competition; Sprache; Belgien